(untitled) (Analysis in Theory and Applications, 2011)
We introduce the definition of q-Stancu operator and investigate its approximation and shape-preserving property. With the help of the sign changes of f (x) and L_n = f ( f ,q;x) the shape-preserving property of q-Stancu operator is obtained.